Direct measurements of counter-streaming flows in a low-shear stellarator magnetic island topology. (26th September 2019) - Perseo, V.; Effenberg, F.; Gradic, D.; König, R.; Ford, O.P.; Reimold, F.; Ennis, D.A.; Schmitz, O.; Sunn Pedersen, T.
Abstract: We report on the first experimental verification of theoretically predicted multiple bundles of counter-streaming plasma flows in the island-divertor scrape-off layer (SOL) of the stellarator Wendelstein 7-X. In the standard toroidal field direction (counter-clockwise when looking from the top) experiments, the overall structure of the SOL flows, such as flow directions, the number of flow bundles and the magnitude of the flow velocities, are consistent with numerical predictions obtained with EMC3-EIRENE. However, the modelling does not predict changes of the flow patterns with reversal of the magnetic field direction, which are experimentally observed. This indicates that additional relevant physics, such as particle drifts, will need to be incorporated into the numerical model to better describe the whole stellarator scrape-off layer behaviour.